2019
DOI: 10.1002/cre2.263
|View full text |Cite
|
Sign up to set email alerts
|

Implant stability in patients treated with platelet‐rich fibrin and bovine bone substitute for alveolar ridge preservation is associated with peripheral blood cells and coagulation factors

Abstract: Aims The aim of the present study was to assess the association between dental implant stability and peripheral blood cell composition and levels of coagulation factors in patients treated with alveolar ridge preservation with platelet‐rich fibrin (PRF) and bovine bone substitute. Materials and methods Fifty patients were included between 2015 and 2017. PRF was prepared from autologous blood, in which blood cells and coagulation factor levels were measured. PRF and bovine bone were placed in the socket, follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
2
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 33 publications
1
2
0
1
Order By: Relevance
“…As assessed in a recent publication of our study group, increased implant primary stability might be due to a presumed stimulation of coagulation factors. 48 Our findings were confirmed by the results of a randomized controlled clinical trial, displaying similar beneficial effects of PRF on implant primary stability. 49 As recently shown by Tarnow and colleagues, bovine bone substitute is working well, when used as augmentation material for ridge preservation immediately after tooth extraction, as we performed in our study.…”
Section: F I G U R E 4 High Correlation Between Both Devices In Bucco-oral (Bo) Directionsupporting
confidence: 81%
“…As assessed in a recent publication of our study group, increased implant primary stability might be due to a presumed stimulation of coagulation factors. 48 Our findings were confirmed by the results of a randomized controlled clinical trial, displaying similar beneficial effects of PRF on implant primary stability. 49 As recently shown by Tarnow and colleagues, bovine bone substitute is working well, when used as augmentation material for ridge preservation immediately after tooth extraction, as we performed in our study.…”
Section: F I G U R E 4 High Correlation Between Both Devices In Bucco-oral (Bo) Directionsupporting
confidence: 81%
“…According to the literature, the application of PRF has improved the repair of dental pulp, reconstruction of tooth structure, wound healing, implant osseointegration and healing of periodontal lesions in dentistry (12,15,16). A systematic review confirmed the possible potential benefits of platelet concentrates in the treatment of teeth replantation.…”
Section: Discussionmentioning
confidence: 99%
“…351 There is no evidence to suggest that bleeding disorders contraindicate receiving dental implants in medically impaired individuals; however, these individuals may be at risk of blood loss and long-term bleeding. 352 von Willebrand factor may be a significant modulator of implant stability, according to research by Brouwers et al 353 Fénelon et al 354 found that guided implant surgery enabled a minimally invasive approach and prevented patient bleeding issues.…”
Section: Von Willebrand Diseasementioning
confidence: 99%